Effects of hospital early childcare intervention in young children with cancer. Issue 3 (3rd July 2022) - Zucchetti, G.; Ciappina, S.; Geuna, T.; Nichelli, F.; Biondi, A.; Camera, F.; Ripaldi, M.; Fagioli, F.
ABSTRACT : Purpose: Oncological diseases, especially if experienced in the first 3 years of life, expose young children to conditions of serious physical and emotional stress causing delays in their physical development, cognitive acquisitioning and issues related to their emotional and social functioning. This study examines the effects of the participation in an early childcare intervention to support the children's development, which was proposed to children from 0 to 36 months, at the moment of cancer diagnosis in their hospital setting. Method: A prospective multicenter programme was offered to young children (<3 years) newly diagnosed with cancer. These children were treated in three pediatric oncology centers affiliated to the Italian Association of Pediatric Hematology-Oncology. The children's strengths and weaknesses, in different developmental areas, were examined pre-programme and 6 months post-programme. Results: Fifty-three young children were enrolled in the study. The data showed that at the moment of diagnosis the majority of the children demonstrated low scores across all the abilities in the subscales examined, highlighting a mental age below their chronological age (ΔT0 = 3.5 months). However, post-programme, the children were shown to have significantly reduced the gap between their chronological and mental age (ΔT1 = 1 month), demonstrating improvements in all their developmental abilities. Conclusion: The study confirms significant implications for early childcare programmes, delivered in hospitals for young children with cancer, in terms of support for their ongoing physical, cognitive and social development. Therefore, the study demonstrated the necessity, for all pediatric oncology centers, to invest in early childhood education programmes.